Parvovirus B19 infection, hepatitis C virus infection, and mixed cryoglobulinaemia. Issue 7 (1st July 1998) - Cacoub, Patrice; Boukli, Narjis; Hausfater, Pierre; Garbarg-Chenon, Antoine; Ghillani, Pascale; Thibault, Vincent; Musset, Lucile; Huraux, Jean Marie; Piette, Jean-Charles
Abstract : BACKGROUND: Infection with human parvovirus B19 (B19) has been reported in a few patients with various vasculitis syndromes. Mixed cryoglobulinaemia (MC), a model of small vessel size vasculitis, may result from numerous infectious diseases, particularly hepatitis C virus (HCV) infection. AIM: To assess the prevalence of seric B19 infection markers in a large series of patients with MC, with or without HCV infection. PATIENTS AND METHODS: Sixty four patients were studied: essential MC (EMC, n = 19), MC associated with non-infectious diseases (non-essential MC, n = 9), and patients with HCV infection with (HCV-MC, n = 18) or without MC (HCV-no-MC, n = 18). Patients were considered to have MC if two successive determinations of their serum cryoglobulin concentration were above 0.05 g/l. Serum samples were analysed for specific IgG and IgM antibodies to B19 by enzyme immunoassay. B19 DNA detection was performed by polymerase chain reaction using a set of primers located in the VP1 gene, separately in serum and in cryoprecipitates to investigate a possible capture of B19 DNA in cryoprecipitate. The study also looked for a possible enrichment for of IgG antibodies to B19 in MC. RESULTS: The presence of specific IgG antibodies to B19 was found in 68% EMC, 56% non-essential MC, 78% HCV-MC, and 78% HCV-no-MC. No patient of either group had specific IgM antibodies to B19, or B19 DNA in serum or in cryoprecipitate. Overall, IgG antibodies to B19 were found in 46 of 64 (72%) serum samples, a prevalence quite similar to the prevalence in general adult population (> 60 %). A specific enrichment of IgG antibodies to B19 in the MC was not found. CONCLUSION: These results suggest that B19 infection is neither an aetiological factor of EMC, nor a cofactor that may lead to MC production in patients with chronic HCV infection.